Fatores de influência na avaliação dos observatórios sociais do Brasil sob a perspectiva da gestão de informação - Lisandra Guerrero Perez (2016)
This research aims to identify the most influential factors to evaluate the Brazilian social observatories understood as informational surveillance systems. The fundamental importance of this study lies in the absence of specific parameters for the evaluation of these systems from the perspective of Information Management. An analysis of six social observatories was held in Brazil [Social Observatory of Brazil, Observatory of Public Policies for Agriculture Centre of Information Management, Metropolis Observatory, Observatory Itaú Cultural and Observatory of Cultural Diversity], taking into account the documentary approach of the evaluation of Digital Information Resources in the literature. This research consists of two stages to achieve the overall objective proposed, the first stage of direct observation of the selected sample, comprising the identification of the general characteristics of the chosen observatories (place and year of creation, the proposed objectives and services and products provided information) the classification of these according to the selected approach and analysis of the behavior of the parameters established by reference in this research (Kapoun, Codina and the Electronic Government Department of Brazil). In the second stage were applied -adaptation questionnaires of CyberGuides- calls to internal and external users of these social observatories to determine the points in common and different in each case. The research concluded with the methodological triangulation of these two steps and the determination of the most significant factors to evaluate the Brazilian social observatories. The Quality of Information, the Currency of Information and the Information Providers are the three parameters most influence on the evaluation of these informational monitoring systems. These most influential factors contribute to the effective and correct evaluation of the Brazilian social observatories to support the generation of knowledge and the development of social intelligence in informational surveillance systems.